PENGEMBANGAN E-BOOK INTERAKTIF BERORIENTASI PRINSIP-PRINSIP PENDIDIKAN PEMBANGUNAN BERKELANJUTAN (ESD) PADA MATERI EKOSISTEM MATA PELAJARAN BIOLOGI KELAS X SMA - Putu Mita Cahyani; I Wayan Sukra Warpala; Ni Putu Sri Ratna Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Research and Development (R&D) method with the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The developed product was an interactive e-book containing learning materials, images, illustrations, videos, interactive activities, and articles on environmental issues integrated with ESD principles. The validity test involved media experts and subject-matter experts, while the practicality test involved one biology teacher and 35 students. The data were analyzed descriptively to determine the validity and practicality of the product. The results showed that: (1) the development process produced an interactive e-book learning medium oriented toward ESD principles on ecosystem topics; (2) the product achieved a validity score of 1.00 from both media and subject-matter experts, indicating a very valid category; and (3) the practicality test results showed percentages of 97.33% from the teacher and 86.67% from the students, both categorized as very practical. Therefore, the ESD-oriented interactive e-book developed in this study was found to be valid and practical for use in biology learning activities on ecosystem topics.